Enhancing oxygen transport in the ionomer film on platinum catalyst using ionic liquid additives - Linhao Fan; Yun Wang; Kui Jiao (Fundamental Research, 2022)
The O2 permeation barrier across the nanoscale ionomer films on electrocatalysts contributes to a major performance loss of proton exchange membrane (PEM) fuel cells under low Pt loading. Enhancing O2 transport through the ionomer films is essential for developing low Pt loading catalyst materials in high-performance PEM fuel cells. This study found that adding an ionic liquid (IL) can effectively mitigate the dense ionomer ultrathin sublayer formed on the Pt surface, which severely hinders O2 transport to the catalyst sites. The molecular dynamics simulation results show that adding the IL significantly alters the ionomer ultrathin sublayer structure by inhibiting its tight arrangement of perfluorosulfonic acid chains but scarcely impacts the ultrathin sublayer thickness. Additionally, the IL addition provides a larger free space for O2 dissolution in the ultrathin sublayer. Consequently, due to IL molecules’ presence, the O2 density in the ultrathin sublayer on the Pt surface is improved by an order of magnitude, which will benefit the catalytic efficiency, and the O2 permeation flux across the ionomer film is increased by up to 8 times, which will reduce the O2 transport loss of the catalyst layer.